2005
DOI: 10.1074/jbc.m412211200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the PTPL1/FAP-1 Human Tyrosine Phosphatase Mutated in Colorectal Cancer

Abstract: Protein-tyrosine phosphatase-L1 (PTPL1, also known as FAP-1, PTP1E, PTP-BAS, and PTPN13) is mutated in a significant number of colorectal tumors and may play a role in down-regulating signaling responses mediated by phosphatidylinositol 3-kinase, although the precise substrates are as yet unknown. In this study, we describe a 1.8 Å resolution crystal structure of a fully active fragment of PTPL1 encompassing the catalytic domain. PTPL1 adopts the standard PTP fold, albeit with an unusually positioned additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 39 publications
(41 reference statements)
4
37
0
Order By: Relevance
“…In HeLa cells, PTPL1 localizes to the centrosomes during metaphase and to the midbody during cytokinesis [14]. Even though the PTP domains of protein tyrosine phosphatases share a high degree of sequence similarity [15], the crystal structure of the PTP domain of PTPL1 reveals a secondary phosphotyrosine binding pocket next to the active site, which is similar to that found in the structure of PTP1B [16]. Consistent with a functional role for this pocket in substrate recognition, monophosphorylated substrates are dephosphorylated by PTPL1 more slowly when compared to bi-or tri-phosphorylated substrates [16].…”
Section: Structurementioning
confidence: 50%
See 2 more Smart Citations
“…In HeLa cells, PTPL1 localizes to the centrosomes during metaphase and to the midbody during cytokinesis [14]. Even though the PTP domains of protein tyrosine phosphatases share a high degree of sequence similarity [15], the crystal structure of the PTP domain of PTPL1 reveals a secondary phosphotyrosine binding pocket next to the active site, which is similar to that found in the structure of PTP1B [16]. Consistent with a functional role for this pocket in substrate recognition, monophosphorylated substrates are dephosphorylated by PTPL1 more slowly when compared to bi-or tri-phosphorylated substrates [16].…”
Section: Structurementioning
confidence: 50%
“…Even though the PTP domains of protein tyrosine phosphatases share a high degree of sequence similarity [15], the crystal structure of the PTP domain of PTPL1 reveals a secondary phosphotyrosine binding pocket next to the active site, which is similar to that found in the structure of PTP1B [16]. Consistent with a functional role for this pocket in substrate recognition, monophosphorylated substrates are dephosphorylated by PTPL1 more slowly when compared to bi-or tri-phosphorylated substrates [16]. The five PDZ domains within PTPL1 are responsible for direct binding to interacting proteins, which could either directly recruit phosphatase substrates or provide a multi-protein scaffold for the indirect binding of substrate proteins.…”
Section: Structurementioning
confidence: 76%
See 1 more Smart Citation
“…Although several studies have identified potential substrates for PTPL1, among which ephrin B is the most documented (25), our study is the first that associates in vivo dephosphorylation and functional assays with in vitro and in vivo substrate trapping experiments. A crystal structure study of the PTPL1 catalytic domain shows that this enzyme, like PTP1B, interacts with and preferentially dephosphorylates bisphosphorylated insulin receptor peptides (26). However, specificity of PTPL1 for peptides from other multiphosphorylated proteins implicated in this transduction pathway, like IRS-1, has not yet been tested.…”
Section: Discussionmentioning
confidence: 99%
“…PTPL1, also called PTP-BAS (31), hPTP1E (4), or Fasassociated phosphatase-1 (FAP-1) (43), is one of the largest protein tyrosine phosphatases with 2,485 amino acids (3). It contains a kinase noncatalytic C-lobe domain and a four-pointone/ezrin/radixin/moesin domain in the NH 2 terminus, five PDZ domains between residues 1102 and 1990, and a protein tyrosine phosphatase domain in the COOH terminus (10,13,48). The four-point-one/ezrin/radixin/moesin domain may be necessary for targeting of PTPL1 to the apical surface of the plasma membrane (13), and the PDZ domains play a role in regulating the intracellular localization of PTPL1 and its interaction with other substrates and proteins (22,25,26).…”
mentioning
confidence: 99%